Molecular diagnosis and phylogeographic analysis of Trypanosoma evansi in dogs (Canis lupus familiaris) suggest an epidemiological importance of this species in Colombia (2017)
Surra disease is a zoonosis caused by Trypanosoma (Trypanozoon) evansi, a salivary trypanosome, originally from Africa, which affects a wide range of mammalian worldwide. Dogs are highly susceptible to T.